Development of mathematical model for hydraulic fracturing design - Md Yusof, M.A. (Springer Verlag, 2015)
Hydraulic fracturing has been proposed as one of the stimulation techniques to economically increase oil and gas production. The design of hydraulic fracturing must make allowances for various considerations, parameters, and complicated calculations. Therefore, this paper presents a simple and fast mathematical model for hydraulic fracturing design treatment. The objective of this project was to develop a mathematical model for hydraulic fracturing design and run case studies for model verification and validation. Mathematical model for hydraulic fracturing design was coded. The code has been verified using several case studies with pronounced rate of success. Verification of mathematical model for hydraulic fracturing design has established a slight percentage differences between the calculated values in the model and manual hand calculation while mathematical model validation have established a very small percentage differences between the calculated values and the field data values. In conclusion, this project will be able to predict the optimization of hydraulic fracturing before conducting any hydraulic fracturing stimulation for the well in the field. Â© 2014, The Author(s).